KEANEKARAGAMAN JENIS EKHINODERMATA DI PERAIRAN MOROTAI, MALUKU UTARA - Eddy Yusron (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2014)
Fauna Of Ekhinodermata Of Coastal Water Of Morotai Part Of South, Maluku Utara. Coastal water of Morotai is included in sub-province of North Halmahera, is recognized to have variety of invertebrate especially from group of echinoderm. The result from three location were found 22 species of echinoderm which included in 4 class which belong to Holothuroidea represented by 5 species, class of Echinoidea 6 species, class of Asteroidea 6 species and class of Ophiuroidea 5 species.